Applying Health Belief Model to Unveil Employees' Workplace COVID-19 Protective Behaviors: Insights for the Hospitality Industry - Rezapouraghdam, Hamed; Karatepe, Osman M. (Tech Science Press, 2020)
The overwhelming majority of the countries around the globe have witnessed severe cases of the COVID-19 outbreak. Unfortunately, many countries are still beset with such an infectious disease. Despite the fact that there is currently no specific approved cure for this deadly infection, restrictions (e.g., lock-down and border closing) are gradually eased. Meanwhile, businesses are reopening and outdoor leisure activities are about to start again based on strict health, social distancing, and hygiene rules. However, as we still have a long way to reach an ultimate treatment for such deadly virus, changing human behavior sounds the best defense in tackling this challenge till a vaccine is developed for protection against COVID-19. With this realization, using Health Belief Model as the theoretical underpinning, our study endeavors to unveil employees' adherence to protective health behaviors (PHBs) in the hospitality industry, which is known as a people-focused, labor-intensive, and service-oriented business. This is so crucial since there is a high degree of (frequent) interaction between employees and customers in hotels. Moreover, such establishments are known as areas where customers engage in a variety of activities that make health concerns even more crucial. To achieve the objectives of this research, we used secondary data obtained from one of the largest hotel-related online communities in the world: the 'Tales from the front desk'. Using template analysis approach, 1680 employees' comments were examined. The results revealed that hotel employees found themselves at high risk of being infected and several obstacles that impeded their PHBs in the workplace were identified. Our study will provide momentous implications about PHBs against COVID-19 for the hospitality industry.
Keywords: COVID-19; hospitality industry; health belief model; employee protective behavior